Pericles, Prince of Tyre: Transforming a Shakespeare Play for Gamified Experience - Hannes Rall; Emma Harper ([sic])
This paper is rooted in an exploration of an ongoing research project to produce a VR game based on Shakespeare’s lesser-known romance Pericles, Prince of Tyre. We argue that the play, a maritime travelogue recounting the story of a family separated at sea and brought together again by fate, is well suited for the demands of gamification, offering rich potential for first-person problem-solving, self-discovery, and world exploration. While its episodic nature, diversity of settings, and unexpected narrative trajectory have challenged those wishing to present the play on the traditional stage, we demonstrate how approaching the text through the lens of immersive gamified media offers the opportunity to re-evaluate and reconsider the “flawed” perception of the text. The paper takes our project as a case study to outline how we approached the process of adapting the original play for gamification, framing our project within the broader context of both game adaptations of Shakespeare’s other works and previous creative, experimental adaptations of Pericles. In particular, we highlight how our practice-led research approach and partnership between animators, technical developers, and researchers at Nanyang Technological University, Singapore, and leading Shakespeare scholars associated with The Shakespeare Institute at the University of Birmingham, UK, brings together creative production, technical development, and academic research to create an experience that is both entertaining and offers an innovative interrogation of Shakespeare’s original plot and language. We hope the discussion offers valuable insight into both novel approaches to the adaptation of Shakespeare’s works and the gamification of classic texts more broadly.